ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUNJUNGAN WISATAWAN DI UMBUL SIBLARAK KLATEN - Nuraini, Candra Dewi; Andriyani, Nur (Jurnal Pariwisata PaRAMA : Panorama, Recreation, Accomodation, Merchandise, Accessbility, 2024)
Klaten Regency, known as the "Regency of a Thousand and One Springs," boasts abundant natural resources, including Umbul Siblarak, which holds significant potential as a nature tourism destination. However, data shows that visits to Umbul Siblarak are relatively low compared to other springs in the region. Further research is needed to identify the factors influencing tourist visits from both consumer and producer perspectives and to provide solutions for improving tourism management. To address the first objective, multiple regression analysis was employed, while qualitative analysis using NVivo software was applied to answer the second objective. Data collection techniques included distributing questionnaires to 100 visitor respondents and conducting Focus Group Discussions (FGDs) with tourism managers. The analysis results revealed that income has a positive and significant effect on tourist visits. Meanwhile, factors such as facility quality, tourist attractions, and promotions have a positive but insignificant impact. Travel costs and accessibility were found to have a negative and insignificant effect on tourist visits. To enhance and support local tourism, strategies such as improving facilities, increasing promotional activities, and enhancing accessibility are necessary. These efforts are expected to make Umbul Siblarak a more attractive tourist destination and contribute to the local economy.